Makna Simbolis Topeng Malangan Lembu Suro Dalam Perspektif Semiotika Visual - Cerly Sudarta Martsidaun (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2024)
The Lembu Suro Mask in the Topeng Malangan tradition is a cultural heritage that contains complex symbolism and deep mythological narratives. This research aims to explore the cultural meanings contained in the visual elements of the mask through Roland Barthes' visual semiotics approach. The analysis was conducted on the denotation and connotation aspects of elements such as color, shape, motif, and expression, and was linked to the Lembu Suro myth in the local tradition of the Malang community. Data were obtained through the observation of mask artifacts, performance art documentation, and interviews with traditional artists. The analysis results show that the red and black colors on the mask symbolize strength, protection, and bravery. The stern face shape with horns resembling a bull reflects characteristics of leadership, bravery, and spirituality. The visual ornaments adorning the mask reinforce its sacred function in rituals, while also serving as a link to the local narrative about the Lembu Suro myth, which emphasizes the values of loyalty, sacrifice, and cosmic harmony. This research asserts that the Lembu Suro Mask not only serves as a medium of aesthetic expression but also functions as a symbol of cultural identity and spirituality of the Malang community. This study contributes to the preservation of traditional craft arts and a deeper understanding of the importance of visual semiotics in representing local values.